Sosialisasi Safety Riding Menurut UU Lalu Lintas pada Siswa SMPN 2 Desa Tengin Baru Penajam Paser Utara - A. M Indriani; Gunaedy Utomo; P. Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Transportation has become a necessity for society to support mobility. a number of roads were built by the government to connect regions and the number of motorized vehicles, especially motorbikes, increased rapidly, but unfortunately this was accompanied by the number of traffic accidents which also continued to increase, which was caused by unsafe driving behavior, lack of understanding and low awareness of applicable traffic regulations. Safety riding socialization needs to be carried out, especially among teenagers who have minimal knowledge of traffic regulations and are still emotionally unstable. In Tengin Baru Village, Kecamatan Sepaku, Kabupaten Penajam Paser Utara, there is an agreement between the police and the community where junior high school students are allowed to ride motorbikes to and from school because there is no public transportation operating in their area. This agreement ultimately resulted in several violations of traffic rules caused by these students, so it was necessary to carry out education and outreach efforts regarding road driving regulations. During the socialization by the Sepaku Sector Police, the students looked enthusiastic when listening to the presentation. The presentation of the material is also equipped with a driving simulation when overtaking another driver on the highway which is demonstrated by student volunteers. During the question session from the police to students to measure the level of students' understanding of the material presented and awareness of Safety Riding, it can be seen that students have understood the material presented and promised to be careful when driving when going to and from school.